A review of the development of interventional devices for mitral valve repair with the implantation of artificial chords - Zhang, Tingchao; Dou, Yichen; Luo, Rifang; Yang, Li; Zhang, Weiwei; Ma, Kangmu; Wang, Yunbing; Zhang, Xingdong (Frontiers in Bioengineering and Biotechnology, 2023)
Mitral regurgitation (MR) was the most common heart valve disease. Surgical repair with artificial chordal replacement had become one of the standard treatments for mitral regurgitation. Expanded polytetrafluoroethylene (ePTFE) was currently the most commonly used artificial chordae material due to its unique physicochemical and biocompatible properties. Interventional artificial chordal implantation techniques had emerged as an alternative treatment option for physicians and patients in treating MR. Using either a transapical or a transcatheter approach with interventional devices, a chordal replacement could be performed transcatheter in the beating heart without cardiopulmonary bypass, and the acute effect on the resolution of MR could be monitored in real-time by transesophageal echo imaging during the procedure. Despite the in vitro durability of the ePTFE material, artificial chordal rupture occasionally occurred. In this article, we reviewed the development and therapeutic results of interventional devices for chordal implantation and discuss the possible clinical factors responsible for the rupture of the artificial chordal material.